Prevalence and patterns of palatine and adenoid tonsilloliths in cone-beam computed tomography images of an Iranian population - Zahra Dalili Kajan; Ali Khalighi Sigaroudi; Majedeh Mohebbi (Wolters Kluwer Medknow Publications, 2016)
Background: Tonsilloliths are calcified concretions that develop in tonsillar crypts. They are usually small and asymptomatic, so they are found accidentally during routine dental radiogrphy procedure. Large tonsilloliths can occur with clinical signs and symptoms. The purpose of this study was to evaluate the prevalence and patterns of palatine and adenoid tonsilloliths in cone-beam computed tomography (CBCT) images. Materials and Methods: In this cross-sectional study, 0.5-mm axial and coronal slices of 134 CBCT images were evaluated to determine the presence of palatine and adenoid calcifications. Their patterns such as being unilateral or bilateral as well as single or multiple and their largest linear sizes were reported. Results: Fifty-four (40.3%) patients with palatine tonsilloliths and 17 (12.7%) with adenoid calcifications were found. Thirty (55.6%) palatine tonsilloliths were unilateral, 19 (35.2%) were detected in the left tonsils. Approximately, 54 cases of 78 palatine calcifications were multiple. Seventeen patients had adenoid calcifications that 41.1% of them were unilateral. Fourteen adenoid calcifications were single. The mean ages of patients with palatine tonsilloliths and adenoid calcifications were 45.59 years and 46.53 years, respectively. The range of linear measurements of palatine tonsil calcifications was 0.9-4.2 mm (2.47-mm mean size) while adenoid calcifications ranged from 0.5 to 2.2 mm (0.95-mm mean size). The level of statistical significant difference was <0.05. Conclusion: Gender did not affect total prevalence, the pattern of tonsilar calcifications and their linear sizes. The prevalence of tonsilloliths increased with aging, but this variable did not have an effect on their linear size.